FAMILY HISTORY STUDY OF THE FAMILIAL COAGGREGATION OF BORDERLINE PERSONALITY DISORDER WITH AXIS I AND NON-BORDERLINE DRAMATIC CLUSTER AXIS II DISORDERS - Zanarini, Mary C. (2009)
The purpose of this study was to assess the familial coaggregation of borderline personality disorder (BPD) with a full array of axis I disorders and four axis II disorders (antisocial personality disorder, histrionic personality disorder, narcissistic personality disorder, and sadistic personality disorder) in the first-degree relatives of borderline probands and axis II comparison subjects. Four hundred and forty-five inpatients were interviewed about familial psychopathology using the Revised Family History Questionnaire—a semistructured interview of demonstrated reliability. Of these 445 subjects, 341 met both DIB-R and DSM-III-R criteria for BPD and 104 met DSM-III-R criteria for another type of personality disorder (and neither criteria set for BPD). The psychopathology of 1580 first-degree relatives of borderline probands and 472 relatives of axis II comparison subjects was assessed. Using structural models for familial coaggregation, it was found that BPD coaggregates with major depression, dysthymic disorder, bipolar I disorder, alcohol abuse/dependence, drug abuse/dependence, panic disorder, social phobia, obsessive-compulsive disorder, generalized anxiety disorder, posttraumatic stress disorder, somatoform pain disorder, and all four axis II disorders studied. Taken together, the results of this study suggest that common familial factors, particularly in the areas of affective disturbance and impulsivity, contribute to borderline personality disorder.